Incretin‐based therapy and acute cholecystitis: a review of case reports and EudraVigilance spontaneous adverse drug reaction reporting database. (2nd March 2016) - Pizzimenti, V.; Giandalia, A.; Cucinotta, D.; Russo, G. T.; Smits, M.; Cutroneo, P. M.; Trifirò, G.
Summary: What is known and objective: Glucagon‐like peptide‐1 (GLP‐1) receptor agonists delay gastric and bowel emptying. A similar inhibitory effect of GLP‐1 on gallbladder motility has been suggested, possibly leading to an increased risk of cholecystitis related to incretin‐based medications, which include GLP‐1 antagonists. Our objective was to review evidence in EudraVigilance, the European spontaneous reporting database and the scientific literature on this issue. Comment: Increasing evidence suggests an association of incretins with gallbladder adverse events. Pharmacovigilance data from EudraVigilance includes 200 serious ADR reports concerning cholecystitis related to the use of incretin‐based therapies. Several mechanisms may explain this increased risk of cholecystitis, including rapid weight loss, inhibition of gallbladder contraction and emptying, reduced bile acids production, modulation of inflammation. What is New and conclusions: The available data suggest the possibility of gallbladder disease in diabetic subjects treated with incretins and highlight the importance of evaluating risk factors for cholelithiasis and gallbladder diseases in patients with diabetes before starting this therapy. Abstract : Increasing evidence suggests an association of incretins with gallbladder adverse events. Pharmacovigilance data from EudraVigilance includes 200 serious ADR reports concerning cholecystitis related to the use of incretin‐based therapies. Several mechanisms may explain this increased risk of cholecystitis, including rapid weight loss, inhibition of gallbladder contraction and emptying, reduced bile acids production, modulation of inflammation.